The effect of neuro-enhancement technology on proprioception in patients with anterior cruciate ligament reconstruction - Du, Hongzhen; Wu, Xipeng; Zhang, Hao; Zhang, Yuxuan; Sun, Zihao; Mi, Baobin; Li, Wei (Frontiers in Human Neuroscience, 2025)
ObjectiveTo investigate whether the neural augmentation technique can induce improvement of proprioceptive performance in Anterior cruciate ligament reconstruction (ACLR) patients.MethodsForty ACLR patients were recruited and randomly assigned to receive either active prefrontal cortex-targeted repetitive transcranial magnetic stimulation (rTMS) or sham stimulation (20 cases per group). All participants underwent the allocated intervention (active or sham rTMS over the prefrontal cortex) and completed standardized balance and proprioceptive assessments both pre- and post-intervention to evaluate the neuromodulatory effects on proprioceptive function in ACLR patients. The alpha level for statistical significance was set at ρ ≤ 0.05 a priori.ResultsIn the rTMS group, the Center of Pressure Area (COPA) and the Center of Pressure Sway (COPS) of the injured limb were significantly reduced before and after repeated transcranial magnetic stimulation (p = 0.002), and the 30° positional sensory stimulation was significantly improved compared with the pre-stimulation period (p = 0.012).ConclusionNeuro-enhancement technology can improve the proprioceptive performance of ACLR patients and thus improve their motor ability.